2014
DOI: 10.1103/physrevb.89.235403
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing forces acting on ZnO polar surfaces: STM, LEED, and DFT

Abstract: New understanding has been reached on competing forces acting to stabilize the polar surfaces of intrinsic ZnO. To compensate an accumulating dipole moment normal to ionic planes, the Madelung electrostatic force and the bonding ability of undercoordinated Zn ions compete to deplete more Zn atoms from the (0001) face and more O atoms from the (0001) face. In this competition, the former mechanism wins because it provides very low energy binding sites for O ions at face-centered-cubic registries on both surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 24 publications
3
72
0
Order By: Relevance
“…The choices of low energy reconstructions without H follow previous investigations [53,57,69,70]. Specifically, on ZnO polar surfaces, although several different surface reconstruction models are proposed by both theoretical calculations and experiments [53,70], the surface energy differences among them are in the order of a few meV/Å 2 [70], suggesting that the (2×2) adatom reconstruction is adequate for our discussions here. For GaN, (2×2) adatom reconstructions were taken into consideration under the condition of N-rich [57].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choices of low energy reconstructions without H follow previous investigations [53,57,69,70]. Specifically, on ZnO polar surfaces, although several different surface reconstruction models are proposed by both theoretical calculations and experiments [53,70], the surface energy differences among them are in the order of a few meV/Å 2 [70], suggesting that the (2×2) adatom reconstruction is adequate for our discussions here. For GaN, (2×2) adatom reconstructions were taken into consideration under the condition of N-rich [57].…”
Section: Methodsmentioning
confidence: 99%
“…The accurate prediction of growth mode will need the absolute energy based on surface reconstructions. In this paper, we adopted surface reconstructions proposed by early STM observations and first principles calculations [53,57,69,70]. In this paper, we follow our cluster and pseudo molecule method [36] strictly.…”
Section: Methodsmentioning
confidence: 99%
“…This observation contradicts the earlier report [29], in which the authors concluded from the thermal desorption study that, although ethanethiol dissociated on ZnO(0001), it adsorbed molecularly on ZnO(0001 _ ) at room temperature. Dissociative adsorption of ethanethiol on ZnO(0001 _ ) can be understood because this ZnO surface undergoes reconstruction to form hexagonal terraces or saw-teeth shaped steps [30,31], whose edges should be truncated by coordinatively unsaturated Zn atoms. These Zn atoms are chemically active to induce S−H cleavage upon thiol adsorption.…”
Section: B Adsorption State Of Ethanethiolmentioning
confidence: 99%
“…Theoretical investigations, however, have proposed several other energetically very similar surface structures and predict a rich surface phase diagram [10][11][12][13][14][15][16], indicating that the surface is highly sensitive to the environmental conditions. Also, experimentally, a wide variety of structures has been observed for similar growth conditions [17][18][19][20][21][22]. Although a lot of effort has been made, and the previously conducted studies contributed significantly to a better understanding of ZnO surfaces, the origin of its structural diversity is not satisfactorily understood, and there are still variables whose impact on the surface phase stability have not been considered so far.…”
Section: Introductionmentioning
confidence: 99%